FAKTOR YANG MEMPENGARUHI EKSPLOITASI PENDAPATAN PADA PEKERJA ANAK DI INDONESIA - Anastasya Rolina Anwar; Wenny Restikasari (Universitas Negeri Surabaya, 2025)
This study analyzes the factors that influence income exploitation among child workers in Indonesia using secondary data from the August 2022 National Labor Force Survey (Sakernas). A quantitative approach and binary logistic regression were applied to test the influence of variables such as regional classification, gender, age, educational status, working hours, and type of work on the likelihood of income exploitation. The results of the analysis show that gender has a significant effect, with female child workers 0.46 times more likely to be exploited than male child workers. Age also has a significant effect, with younger child workers 0.87 times more likely to experience exploitation than older child workers. Child workers who work more than 40 hours per week are 1.65 times more likely to be exploited than those who work ≤ 40 hours per week. In addition, child workers in the informal sector are 2.46 times more likely to be exploited than those in the formal sector. Meanwhile, regional classification and educational status do not have a significant effect on the level of income exploitation of child workers in Indonesia